2020
DOI: 10.1515/npprj-2019-0087
|View full text |Cite
|
Sign up to set email alerts
|

High strength paper from high yield pulps by means of hot-pressing

Abstract: AbstractThe hypothesis is that it should be possible to modify papermaking conditions in line with the softening properties of high yield pulp fibres and achieve similar strength properties to conventional chemical pulp based paper. We therefore investigated the rheological and physical properties of high yield pulp based papers during hot-pressing. Our results confirm that increased temperature combined with sufficient pressure enables permanent densification by softening of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 26 publications
3
38
1
Order By: Relevance
“…Hunt et al [26] studied the influence of pressure on cellulose fibers properties and observed that a drying in a hot press strongly limits the material's shrinkage as well as reduces the product's thickness and water content. Joelsson et al [27] observed that a higher processing temperature and a higher pressure increase the material's density, thus resulting in a lower pores size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunt et al [26] studied the influence of pressure on cellulose fibers properties and observed that a drying in a hot press strongly limits the material's shrinkage as well as reduces the product's thickness and water content. Joelsson et al [27] observed that a higher processing temperature and a higher pressure increase the material's density, thus resulting in a lower pores size.…”
Section: Resultsmentioning
confidence: 99%
“…A higher mould B temperature improves the MPP's Young's Modulus for both initial and after water sorption. Several studies [23,24,27] observed that a higher processing temperature allows the tensile index to be improved as it allows to have a lower WTR and swelling capacity [21,24,37]. Moreover, an even higher temperature used decreases the mechanical properties as given by the results in the drying time of moulds C and D as well as the moulds C and D temperature for the sorption analysis.…”
Section: Mechanical Properties Depending On the Process Parametersmentioning
confidence: 99%
“…Hunt et al [26] studied the influence of pressure on cellulose fibers properties and observed that a drying in a hot press strongly limits the material's shrinkage as well as reduces the product's thickness and water content. Joelsson et al [27] observed that a higher processing temperature and a higher pressure increase the material's density, thus resulting in a lower pores size. Reducing the pores size limits the water uptake and fiber swelling while increasing the cellulose's degree of crystallinity.…”
Section: The Influence Of Process Parameters On the Sorption Propertimentioning
confidence: 99%
“…A higher mould B temperature improves the MPP's Young's Modulus for both initial and after water sorption. Several studies [23,24,27] observed that a higher processing temperature allows the tensile index to be improved as it allows to have a lower WTR and swelling capacity [21,24,30].…”
Section: Mechanical Properties Depending On the Process Parametersmentioning
confidence: 99%
See 1 more Smart Citation